Cell type-specific roles of NLRP3, inflammasome-dependent and -independent, in host defense, sterile necroinflammation, tissue repair, and fibrosis - Honda, Tamisa Seeko Bandeira; Ku, John; Anders, Hans-Joachim (Frontiers in Immunology, 2023)
The NLRP3 inflammasome transforms a wide variety of infectious and non-infectious danger signals that activate pro-inflammatory caspases, which promote the secretion of IL-1β and IL-18; and pyroptosis, a pro-inflammatory form of cell necrosis. Most published evidence documents the presence and importance of the NLRP3 inflammasome in monocytes, macrophages and neutrophils during host defense and sterile forms of inflammation. In contrast, in numerous unbiased datasets NLRP3 inflammasome-related transcripts are absent in non-immune cells. However, an increasing number of studies report the presence and functionality of the NLRP3 inflammasome in almost every cell type. Here, we take a closer look at the reported cell type-specific expression of the components of the NLRP3 inflammasome, review the reported inflammasome-dependent and -independent function, and discuss possible explanations for this discrepancy.